PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS PELANGGAN PADA RESTORAN KEUDE MIE ACEH 46 VILLA RENI PAMULANG DI KOTA TANGERANG SELATAN - Auliana Setyaputri, Savira; Haryantini (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of product quality and price on customer loyalty at the Keude Mie Aceh 46 Villa Reni Pamulang Restaurant in South Tangerang City. The method used is a quantitative method. The sampling technique used is Probability Sampling with Random Sampling type. The number of samples used in this research was 96 respondents. Data analysis techniques using instrument tests, namely validity and reliability tests, classic assumption tests, namely normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, simple linear regression test, multiple linear regression test, correlation coefficient test, coefficient of determination test and hypothesis test, namely t test and F test. The results of this research are that product quality has a significant effect on customer loyalty with the regression equation Y = 10.284 + 0.261X1. Hypothesis testing obtained t value > t table (6.978 > 1.661). Price has a significant effect on customer loyalty with the regression equation Y = 6.418 + 0.566X2. Hypothesis testing obtained t value > t table (8.739 > 1.661). Product quality and price simultaneously have a significant effect on customer loyalty with the regression equation Y = 5.306 + 0.94X1 + 0.438X2. Hypothesis testing obtained a value of Fcount > Ftable or (41.108 > 3.094). Thus, it can be concluded that product quality and price have a positive and significant effect on customer loyalty.